2021
DOI: 10.3390/brainsci11050640
|View full text |Cite
|
Sign up to set email alerts
|

Two Faces of a Coin? A Systematic Review of Source Monitoring and Its Relationship with Memory in Autism

Abstract: The ability to discriminate the origin of stimuli, known as source monitoring, is crucial for self–other distinction and the integration of internally generated and externally generated experiences. Despite its valence, evidence on source monitoring in autism is yet scarce and unclear. We systematically reviewed literature concerning source monitoring in autism and its relationship with other constructs, such as memory type, encoding effects, social cognition, general intelligence, and clinical factors. Source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
(131 reference statements)
0
4
0
Order By: Relevance
“…Positive correlation of SM performance and several subsets of cognitive skills were found, but with very few replications (including memory). Besides, it must be noted that >60% of the included studies matched PSY and HC by IQ and yet found important differences in SM between groups, in line with the view that SM and cognition are only partially overlapping constructs 72 …”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Positive correlation of SM performance and several subsets of cognitive skills were found, but with very few replications (including memory). Besides, it must be noted that >60% of the included studies matched PSY and HC by IQ and yet found important differences in SM between groups, in line with the view that SM and cognition are only partially overlapping constructs 72 …”
Section: Discussionmentioning
confidence: 52%
“…Novel approaches suggest that SM may be an objective measure of deeply subjective disorders such as anomalous self‐experiences 53,83 by testing the very notion of self as a “principle of identity.” 69 Based on our findings, we pose that the internal/imagined category of stimuli may be the primary proxy on which the subject relies on when determining its separate existence from the surrounding world, and that this dynamic is fundamentally altered in psychosis. This hypothesis is supported by the fact that reduced SM performance is lower not only in psychosis, but also in at risk mental states, 84 autism 72 and Alzheimer's disease 85 which are conditions where self‐disturbances are relevant. Conversely, no SM deficits have been reported for conditions where self is preserved, such as major depressive disorder 34 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Fourth, Kadlaskar et al [27] compared different aspects of tactile cues between autistic and typically developing children, further underlying the importance of research on sensory processing in this population. Finally, Damiani et al reviewed the literature concerning source monitoring, a crucial skill for self-other distinction and integration between internally-and externally-generated experiences [28].…”
mentioning
confidence: 99%